(3GdCbdjGJ GdGSdGejI aj GdYGde ZjQ GdGSdGej s - (3YOfGf EHQGgje(B, (3geSIs ((3YeGfs (3OGQ GdefGgL ddfTQ hGdJhRjYs, 2023)
(3jYGdL gPG GdcJGH HObI hTehdjI bVjI GdCbdjGJ GdeSdeI GdefJTQI aj eNJda CfMGA GdYGde ZjQ GdESdGej(B. (3jHOC GdcJGH HJbOje deMI YGeI Yf gPg GdCbdjGJ, hjJfGhd JGQjN ONhd GdESdGe Edi bGQGJ GdYGde GdbOjeI hJCKjQg Ydi GdeLJeYGJ GdeMdjI(B. (3ceG jSJYQV GdcJGH GdJMOjGJ hGdeTcdGJ GdJj JhGLg gPg GdCbdjGJ aj HdOGf ZjQ ESdGejI, HOkAG ef GdJejjR GdOjfj hGfJgGkA HGdUYhHGJ aj eeGQSI GdTYGFQ GdOjfjI(B. (3haj GdaUd GdCNjQ, jJYeb GdcJGH aj OQGSI Gdabg GdESdGej GdNGU HGdCbdjGJ, eSJYQkVG GdbhGYO hGdCMcGe GdTQYjI GdJj JfXe MjGJge hYdGbGJge HGdeLJeYGJ GdeMjWI Hge(B. (3jgOa GdcJGH Edi JSdjW GdVhA Ydi gPg GdbVjI GdgGeI, hEjLGO Mdhd YedjI ddeTcdGJ GdJj JhGLggG GdCbdjGJ GdeSdeI aj GdYGde GdeYGUQ(B.s
Keywords: (3GdESdGe (B- (3GdCbdjGJ s; (3Gdabg GdESdGej(B- (3GdCbdjGJ GdESdGejIs